1984
DOI: 10.1111/j.1600-0404.1984.tb07784.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclophosphamide on T lymphocytes and T lymphocyte subsets in patients with chronic progressive multiple sclerosis

Abstract: The lymphocytes in peripheral blood and cerebrospinal fluid of patients with chronic progressive multiple sclerosis (MS) were characterized with monoclonal antibodies to surface antigens of T cells, helper/inducer T cells and suppressor/cytotoxic T cells. The influence of cyclophosphamide treatment on these immune parameters was investigated. Compared to healthy persons, the mononuclear cell fraction of the peripheral blood of patients with chronic progressive MS consisted of normal %s of T cells and helper/in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This confirms earlier reports (19,20,10). The effect of CY is more pronounced on CD4' cells resulting in a decrease of the CD4+/CD8+ ratio.…”
Section: Discussionsupporting
confidence: 94%
“…This confirms earlier reports (19,20,10). The effect of CY is more pronounced on CD4' cells resulting in a decrease of the CD4+/CD8+ ratio.…”
Section: Discussionsupporting
confidence: 94%
“…Cyclophosphamide was one of the first drugs shown to reverse the course of EAE even when given after symptoms appeared (18,19) and provided a rationale for treating patients with MS. Early studies on the immunologic effects of cyclophosphamide demonstrated a decrease in the absolute number of T cells (20), a reduction in circulating B cells (21), a decrease in the synthesis of IgG within the blood-brain barrier (22), and decreased spontaneous proliferation of lymphocytes (23). We have investigated the use of pulse cyclophosphamide to treat progressive MS and found a positive clinical effect in younger patients with actively progressive disease of short duration (24,25), although not all studies of cyclophosphamide therapy found a positive effect (26).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide effectively reduces the number of circulating T and B cells, 25,26 in addition to creating a more favorable cytokine balance, shifting away from autoimmune Th1 responses and reductions in interleukin 12 (IL-12) and interferon gamma (IFN-γ). 27 Cyclophosphamide and its metabolites are also capable of penetrating the blood–brain barrier and can exert direct intrathecal immunologic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophosphamide has a long history in the treatment of MS, having been utilized in some of the first published treatment trials in this condition, 23,24 although at much lower doses than in this study. Cyclophosphamide effectively reduces the number of circulating T and B cells, 25,26 in addition to creating a more favorable cytokine balance, shifting away from autoimmune Th1 responses and reductions in interleukin 12 (IL-12) and interferon gamma (IFN-γ). 27 Cyclophosphamide and its metabolites are also capable of penetrating the blood–brain barrier and can exert direct intrathecal immunologic effects.…”
Section: Discussionmentioning
confidence: 99%